2008
DOI: 10.1074/jbc.m800731200
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210 Modulates Endothelial Cell Response to Hypoxia and Inhibits the Receptor Tyrosine Kinase Ligand Ephrin-A3

Abstract: MicroRNAs (miRNAs) are small non-protein-coding RNAs that function as negative gene expression regulators. In the present study, we investigated miRNAs role in endothelial cell response to hypoxia. We found that the expression of miR-210 progressively increased upon exposure to hypoxia. miR-210 overexpression in normoxic endothelial cells stimulated the formation of capillary-like structures on Matrigel and vascular endothelial growth factor-driven cell migration. Conversely, miR-210 blockade via anti-miRNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
725
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 813 publications
(777 citation statements)
references
References 27 publications
48
725
1
3
Order By: Relevance
“…MiR‐210 promotes angiogenesis and the maturation of vasculature in post‐ischaemic brain tissue by enhancing the expression of Notch, VEGF and vascular endothelial growth factor receptor‐2 (VEGFR‐2) in HUVECs 90. Further research indicated that miR‐210 facilitates angiogenesis through negatively regulating the target gene, ephrin A3, which is an important member of the ephrin angiogenesis regulatory gene family 51, 91, 92. Moreover, a study revealed that isoprenaline enhances the levels of miR‐210, miR‐21 and miR‐1 and decreases those of the lncRNAs maternally expressed 3 (MEG3) and growth arrest‑specific transcript 5 (GAS5), thereby improving angiogenesis 93.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…MiR‐210 promotes angiogenesis and the maturation of vasculature in post‐ischaemic brain tissue by enhancing the expression of Notch, VEGF and vascular endothelial growth factor receptor‐2 (VEGFR‐2) in HUVECs 90. Further research indicated that miR‐210 facilitates angiogenesis through negatively regulating the target gene, ephrin A3, which is an important member of the ephrin angiogenesis regulatory gene family 51, 91, 92. Moreover, a study revealed that isoprenaline enhances the levels of miR‐210, miR‐21 and miR‐1 and decreases those of the lncRNAs maternally expressed 3 (MEG3) and growth arrest‑specific transcript 5 (GAS5), thereby improving angiogenesis 93.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…For example in colorectal cancer, tumour-derived EVs can promote proliferation of endothelial cells and enhance their cell-cycle activities through M-phase related mRNAs, such as those coding for the centromere protein E (CENPE), PDZ binding kinase (PBK) or cyclin-dependent kinase 8 (CDK8) 32 . Additionally, the involvement of vesicular miRNAs in neo-angiogenesis has been studied such as miRNA-210 that exhibited strong pro-angiogenic activity 22,40,83 . Furthermore, miRNA-210 has been observed to suppress the expression of specific genes such as EFNA3 (coding for Ephrin-A3) in endothelial cells, resulting in enhanced neo-angiogenesis 21,39,73 .…”
Section: Evs Set the Place And Time For Neo-angiogenesismentioning
confidence: 99%
“…13 HIF-1alpha induces microRNA-210 (hsa-miR-210) directly through its interaction with its promoter sequence. Validated targets of hsa-miR-210 include the receptor tyrosine kinase ligand ephrin-A3, 14 the transcription factor E2F3, 15 and the DNA repair enzyme RAD52. 16 However, the effect of hsa-miR-210 may depend on the cancer type; whereas high level of expression is an independent prognostic factor in breast cancer, 17 it is frequently deleted in epithelial ovarian cancer.…”
mentioning
confidence: 99%